Ractopamina e arginina na alimentação de suínos - Calixto, Jussara Maria Reis (2012)
The objective of this study was to evaluate the effect of arginine and ractopamine on performance, carcass characteristics, lipid profile and liver histological features in growing and finishing pigs. The experimental design was randomized blocks with three treatments, eight repetitions, two animals per experimental unit, for a total of 24 animals (12 barrows and 12 gilts) with 65 days of age and live weight of 32 ± 0,75 quilogramas .The treatments were divided into: T1: control (C) (isocaloric meal and isocaloric), T2: C + 4 ppm of ractopamine and T3: C + 0.8% arginine.The additives ractopamine and arginine were added to the mash feed and these ad libitum for 89 days and 46 days of growth phase and 43 days from the termination phase. On reaching 150 days of age, the animals were slaughtered. We evaluated animal performance (average daily feed intake, average daily gain in weight and feed conversion) weighing the animals at the beginning and end of each phase and the rations offered. At slaughter blood samples were collected for biochemical analysis of lipid profile and liver slices for histological examination. The carcasses were hot and heavy after 24 hours refrigerated, carcass length, backfat thickness and loin eye area, were measured in hot carcass. Ractopamine supplementation improved the average feed intake during the growing phase (P <0.05), and average daily weight gain in crescimemto and finishing phases (P <0.05), without however changing other variables, carcass characteristics (P> 0.05) and lipid profile (P> 0.05). The addition of arginine did not affect performance (P> 0.05), carcass traits (P> 0.05) and lipid profile (P> 0.05).Therefore, it was characterized the beneficial effect of ractopamine on reducing the average consumption ration in the growth phase and increased average daily weight gain and decreased average daily consumption of feed during the finishing phase .